2016
DOI: 10.1097/md.0000000000004730
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, serum total cholesterol, and risk of gastric high-grade dysplasia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
8
0
1
Order By: Relevance
“…Chronic gastritis then can convert into gastric atrophy, intestinal metaplasia and dysplasia, and finally transformed into GC . Previous studies reported that overweight and obesity were associated with dysplasia and intestinal metaplasia, and it is possible that the pro‐inflammatory effects of obesity may then contribute to the progression of these inflammatory states toward cancer. Other studies found associations between underweight and intestinal metaplasia and an inverse relationship between BMI and atrophic gastritis, whereby low BMI may then be reflecting malabsorption from the condition of severe gastritis .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic gastritis then can convert into gastric atrophy, intestinal metaplasia and dysplasia, and finally transformed into GC . Previous studies reported that overweight and obesity were associated with dysplasia and intestinal metaplasia, and it is possible that the pro‐inflammatory effects of obesity may then contribute to the progression of these inflammatory states toward cancer. Other studies found associations between underweight and intestinal metaplasia and an inverse relationship between BMI and atrophic gastritis, whereby low BMI may then be reflecting malabsorption from the condition of severe gastritis .…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports which show a positive association of high blood cholesterol with an increased risk of gastric cancer. The risk of gastric dysplasia (pre-cancerous lesion which is often considered as a penultimate stage of gastric cancer) was increased in patients with elevated blood cholesterol levels [149 , 150] . Earlier studies from Pih GY, et al.…”
Section: Role Of Cholesterol In Various Cancermentioning
confidence: 99%
“…However, previous studies have shown contradictory results about the effect of lipids on various cancers, including gastric cancer. TC had negative [ 4 , 5 ], positive [ 6 ], or no correlation [ 7 ] with gastric neoplasms. In addition, few studies have focused on the relationships of TG, LDL-C, or apolipoproteins with gastric cancer, as most reports have been based on ancillary findings observed in a study of metabolic syndrome or statins.…”
Section: Introductionmentioning
confidence: 99%